FACTORS THAT INFLUENCE THE CORPORATE VALUE LISTED IN LQ 45 - Dwi Purwaningrum; Shena Ananda Putri; Ayu Miranda Limbong (Accounting Profession Journal (APAJI))
Research Aims: This study examines the impact of liquidity and decision of investmenton corporation value in LQ-45 companies listed on the Indonesia Share Exchange (IDX) between 2019 and 2023.